Potential Ago2/miR-3068-5p Cascades in the Nucleus Accumbens Contribute to Methamphetamine-Induced Locomotor Sensitization of Mice - Liu, Dan; Liang, Min; Zhu, Li; Zhou, Ting-ting; Wang, Yu; Wang, Rui; Wu, Fei-fei; Goh, Eyleen L. K.; Chen, Teng (Frontiers in Pharmacology, 2021)
Dysregulation of microRNA (miRNA) biogenesis is involved in drug addiction. Argonaute2 (Ago2), a specific splicing protein involved in the generation of miRNA, was found to be dysregulated in the nucleus accumbens (NAc) of methamphetamine (METH)-sensitized mice in our previous study. Here, we determined whether Ago2 in the NAc regulates METH sensitization in mice and identified Ago2-dependent miRNAs involved in this process. We found a gradual reduction in Ago2 expression in the NAc following repeated METH use. METH-induced hyperlocomotor activity in mice was strengthened by knocking down NAc neuronal levels of Ago2 but reduced by overexpressing Ago2 in NAc neurons. Surprisingly, miR-3068-5p was upregulated following overexpression of Ago2 and downregulated by silencing Ago2 in the NAc. Knocking down miR-3068-5p, serving as an Ago2-dependent miRNA, strengthened the METH sensitization responses in mice. These findings demonstrated that dysregulated Ago2 in neurons in the NAc is capable of regulating METH sensitization and suggested a potential role of Ago2-dependent miR-3068-5p in METH sensitization.